2003
DOI: 10.1046/j.1365-8711.2003.06349.x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional convection simulations of the outer layers of the Sun using realistic physics

Abstract: This paper describes a series of three‐dimensional simulations of shallow inefficient convection in the outer layers of the Sun. The computational domain is a closed box containing the convection–radiation transition layer, located at the top of the solar convection zone. The most salient features of the simulations are that: (i) the position of the lower boundary can have a major effect on the characteristics of solar surface convection (thermal structure, kinetic energy and turbulent pressure); (ii) the widt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 26 publications
5
102
0
Order By: Relevance
“…These models utilize an extended Kolmogorov spectrum with a modified Gaussian frequency factor. The acoustic energy flux is found to be dependent on the mixinglength parameter α, for which we use α = 2 as indicated by solar studies (Steffen 1993;Robinson et al 2003). Similar investigations in the case of longitudinal flux-tube waves have been presented by Ulmschneider & Musielak (1998).…”
Section: (Magneto-)hydrodynamic Model Computationsmentioning
confidence: 61%
“…These models utilize an extended Kolmogorov spectrum with a modified Gaussian frequency factor. The acoustic energy flux is found to be dependent on the mixinglength parameter α, for which we use α = 2 as indicated by solar studies (Steffen 1993;Robinson et al 2003). Similar investigations in the case of longitudinal flux-tube waves have been presented by Ulmschneider & Musielak (1998).…”
Section: (Magneto-)hydrodynamic Model Computationsmentioning
confidence: 61%
“…The systematic growth in error at higher frequencies (higher n) is associated with the inherent uncertainties in the modeling of the superadiabatic layer of the Sun via the mixing-length theory. Li et al (2002) have shown that much of this discrepancy can be eliminated by incorporating the results of numerical stellar convection in both the model and the p-mode frequency calculation (see also Rosenthal et al 1999;Robinson et al 2003). We assume that the stellar model frequency uncertainties are similar to the discrepancies found between our solar model frequencies and the observed frequencies.…”
mentioning
confidence: 59%
“…On the other hand, the continuous growth of computer power is allowing us to solve this problem numerically using only the basic laws of hydrodynamics, including radiative transfer in the energy equation. A better understanding of solar and stellar granulation is thus possible through numerical simulations (e.g., Nordlund & Dravins 1990;Freytag et al 1996;Stein & Nordlund 1998;Asplund et al 1999;Ludwig et al 1999;Robinson et al 2003;Vögler 2004;Asplund 2005;Collet et al 2006Collet et al , 2007Nordlund et al 2008).…”
Section: Introductionmentioning
confidence: 99%